Duet: A Mobile Application to Facilitate Parents in Practicing Coparenting - Jessica Christina Widhigdo; Jenny Lukito Setiawan; Mychael Maoeretz Engel; Lisa Indriati (Universitas Pendidikan Ganesha, 2024)
Increasing achievement motivation in children, parents need tools to educate them about co-parenting and how to develop achievement motivation in children. Parents also need a means to discuss their parenting patterns and monitor their children. This research aims to develop a coparenting-based mobile application. This type of research is development research that follows the ADDIE development model. The data collection method uses a questionnaire. The data collection instrument uses a questionnaire sheet. The validation sheet is filled in by psychology, technology, and design experts. 92 parents of elementary school students also tested this application in grades 4-6. The data analysis technique uses qualitative and quantitative descriptive analysis. The results of the research, namely expert validation, show that the Duet application has content that is very suitable and useful for helping parents improve co-parenting in order to develop children's achievement motivation (96.30%), is very technologically reliable (83.20%), and has very good design effectiveness (93.33% ). The results of trials on parents showed that this application was very well accepted by parents (81.09%). It was concluded that DUET, a co-parenting-based mobile application, can be used as a tool for parents to develop co-parenting to increase children's achievement motivation. The implication of this research is that the coparenting-based mobile application developed can be used by teachers and parents to improve children's achievement.